Untargeted metabolomic profiling, nutritional composition and enzyme changes on bigeye tuna (Thunnus obesus) during cold storage by UPLC-MS coupled with logistic regression - Xinyun Wang; Zixuan Zhao; Jun Yan; Jing Xie (Food Science and Human Wellness)
Bigeye tuna is a protein-rich fish that is susceptible to spoilage during cold storage, however, there is limited information on untargeted metabolomic profiling of bigeye tuna concerning spoilage-associated enzymes and metabolites. This study aimed to investigate how cold storage affects enzyme activities, nutrient composition, tissue microstructures and spoilage metabolites of bigeye tuna. The activities of cathepsins B, H, L increased, while Na+/K+-ATPase and Mg2+-ATPase decreased, α-glucosidase, lipase and lipoxygenase first increased and then decreased during cold storage, suggesting that proteins undergo degradation and ATP metabolism occurs at a faster rate during cold storage. Nutrient composition (moisture and lipid content), total amino acids decreased, suggesting that the nutritional value of bigeye tuna was reduced. Besides, a logistic regression equation has been established as a food analysis tool and assesses the dynamics and correlation of the enzyme of bigeye tuna during cold storage. Based on untargeted metabolomic profiling analysis, a total of 524 metabolites were identified in the bigeye tuna contained several spoilage metabolites involved in lipid metabolism (glycerophosphocholine and choline phosphate), amino acid metabolism (L-histidine, 5-deoxy-5′-(methylthio)adenosine, 5-methylthioadenosine), carbohydrate metabolism (D-gluconic acid, α-D-fructose 1, 6-bisphosphate, D-glyceraldehyde 3-phosphate). The results of tissue microstructures of tuna showed a looser network and visible deterioration of tissue fiber during cold storage. Therefore, metabolomic analysis and tissue microstructures provide insight into the spoilage mechanism investigations on bigeye tuna during cold storage.